2016
DOI: 10.4172/2155-9600.1000541
|View full text |Cite
|
Sign up to set email alerts
|

Translation of Evidence to Clinical Practice for Use of Meal Replacements in Weight Loss and Obesity-lessons Learned from Research Studies

Abstract: Meal replacements have been shown to be effective in assisting weight loss in many clinical trials; however, adherence is a major determinant of the reported success. Characterizing how meal replacements were used for weight loss in clinical studies can assist healthcare providers to replicate efficacy and improve adherence to achieve successful weight loss. This narrative review characterizes the treatment conditions that support meal replacements use for weight loss from 45 clinical trials. From these studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 80 publications
(208 reference statements)
0
4
0
Order By: Relevance
“…A review of interventional studies using MR for weight loss as a part of a low calorie diet plan showed adherence of 50–70% with varied retention between 48 and 100% (16). Inclusion of MR may represent one of the solutions for improving long-term success of weight-reducing diets combined with standard lifestyle changes in overweight free-living subjects, probably due to a simple preparation and general convenience (13).…”
Section: Discussionmentioning
confidence: 99%
“…A review of interventional studies using MR for weight loss as a part of a low calorie diet plan showed adherence of 50–70% with varied retention between 48 and 100% (16). Inclusion of MR may represent one of the solutions for improving long-term success of weight-reducing diets combined with standard lifestyle changes in overweight free-living subjects, probably due to a simple preparation and general convenience (13).…”
Section: Discussionmentioning
confidence: 99%
“…A review reported that self-monitoring in weight loss interventions was necessary to support behavior change for weight loss as it encourages the development of self-regulatory skills, such as evaluating and reinforcing progress made toward a particular behavior. 36 …”
Section: Discussionmentioning
confidence: 99%
“…A prescribed meal plan with meal replacements should last for at least 2 weeks and can be prescribed indefinitely without any laboratory monitoring if it has at least 1200 kcal/day [27•]. However, to most effectively incorporate meal replacements and prevent attrition, regular follow-up is needed to provide continued education, counseling, and track progress [31]. Patients with diabetes especially require intensive self-monitoring of blood glucose [31].…”
Section: A Healthy Meal Planmentioning
confidence: 99%
“…However, to most effectively incorporate meal replacements and prevent attrition, regular follow-up is needed to provide continued education, counseling, and track progress [31]. Patients with diabetes especially require intensive self-monitoring of blood glucose [31].…”
Section: A Healthy Meal Planmentioning
confidence: 99%